Diagnosis of the Laboratories of Physics and Chemistry in the Universidad TÃ©cnica De ManabÃ - Loor, Yadira del Pilar ChÃƒÂ¡vez; CedeÃƒÂ±o, Roxana Jacqueline Panchana; Robaina, Daniel Alfonso (International Research Journal of Management, IT & Social Sciences, 2017)
The following work tries to diagnose the capacities in function of the management of the maintenance of the infrastructure of the laboratories of Physics and Chemistry of the Technical University of ManabÃ, having as reference the external and internal relations of the processes of maintenance, for the fulfillment Of this purpose a strategic diagnosis of the Universidad TÃ©cnica de ManabÃ (UTM) and the identification of the critical relations of the activities of maintenance of the laboratories of Physics and Chemistry of the UTM and its evaluation of the level of integration is realized.